RELATIONSHIP BETWEEN METHYLENE TETRA HYDRO FOLATE REDUCTASE (MTHFR) GENE POLYMORPHISM AND HYPERHOMOCYSTEINEMIA IN STROKE - Raka Widiana, I Gde; -, Tianing; Santoso, Anwar; Ketut Budiarsa, Gusti Ngurah (journal of internal medicine; Vol. 8, No. 3 September 2007)
Cardiovascular disease is a major cause of mortality in Indonesia. Hyperhomocysteinemia (hyper-hcy) is an independent cardiovascular risk factor, which may be due to methylene tetrahydrofolate reductase (MTHFR) deficiency, frequently linked to MTHFR gene mutation. This case-control study examined the relationship between homocysteine (hcy), folate, and vitamin B12 plasma concentrations with C677T mutation of MTHFR gene among 20 haemorrhagic and non-haemorrhagic stroke patients aged 18-55 years, in Sanglah Hospital, Denpasar. 10 age-matched controls were selected via random sampling of 1 of 4 neighbours; all subjects were Balinese. Hyper-hcy (X2: 5.4; PR: 1.8; 95% CI: 1.0-2.7; p=0.03), hypertension (X2: 13.12; PR 2.66; 95%CI 1.41 to 5.02; p=0.00) were associated with increased risk of stroke. There were no significant correlation between plasma hcy levels and plasma folate and vitamin B12 levels as co-factors of hcy metabolism. Low plasma vitamin B12, smoking, alcohol drinking, and hypertension tend to be determinant factors of hyper-hcy. This study found no mutation on 677 from C to T (C677T), however there were substitution in nucleotides among stroke and controls, with or without producing chances of amino acids, including: 1) G659A substitution that caused changing in amino acid from glutamine to glycine found in 1 stroke patients with hyper-hcy; 2) A660G substitution that cause changing in amino acid from glutamine to glycine found among all control subjects and among 3 stroke patients, one of whom had hyper-hcy; and 3) A661G substitution that cause changing in amino acid from lysine to glutamine found in one stroke patients with normo-hcy. Some variations were also found in nucleotide 659 and 660, however, did not produce changing in amino acid. Whether this substitution is a kind of polymorphism that specific to Balinese ethnicity needs a further study to answer.
Keywords: methylene tetra hydro folate reductase (MTHFR), gene polymorphism and hyperhomocysteinemia, stroke